Understanding the Current-Voltage Behavior of High Temperature Solid Oxide Fuel Cell Stacks. Issue 13 (1st January 2017) - Lang, M.; Bohn, C.; Henke, M.; Schiller, G.; Willich, C.; Hauler, F.
Abstract : High temperature solid oxide fuel cell (SOFC) stacks are highly efficient and environmentally friendly electrochemical systems, which convert the chemical energy of fuel gases with oxygen from air directly into electrical energy. During operation of SOFC stacks under system operating conditions pronounced temperature and fuel gas composition gradients along the cell area and along the height of the stack occur. Therefore, in contrast to SOFC cells, the electrochemical behavior of SOFC stacks is much more complex and has not sufficiently been studied. Specially, a shortcoming exists in terms of understanding the homogeneity, performance loss mechanisms, and various resistances and overvoltages within the stack repeat components. Therefore, this paper focuses on the improvement of the understanding and of the interpretation of different current-voltage curves of solid oxide fuel cell stack repeat units. Three different cases are discussed: repeat units with high power performance, with high cell contact resistance and with high fuel utilization. The stacks were investigated by current-voltage curves, electrochemical impedance spectroscopy and gas analysis. In order to understand the electrochemical behavior of these three cases both experimental and modeling results are presented, compared and discussed.